Evaluation of 5-fluorouracil-treated lung cancer cells by atomic force microscopy. Issue 39 (25th September 2019) - Jiang, Xiaolin; Ma, Ke; Hu, Cuihua; Gao, Mingyan; Zhang, Jiashuo; Wang, Ying; Chen, Yujuan; Song, Zhengxun; Wang, Zuobin
Abstract : The drug efficacy and side-effect of 5-fluorouracil for non-small cell lung cancer cells were studied by atomic force microscopy. Abstract : Atomic force microscopy (AFM) can be used to obtain the physical information of single live cancer cells; however, the physical changes in live cells with time based on AFM remain to be studied, which play a key role in the evaluation of the efficacy and side effects of drugs. Herein, the treatment of the A549 cell line with the anticarcinogen 5-fluorouracil has been discussed based on the AFM analysis of their continuous physical changes, including their surface morphology, height, adhesion and Young's modulus, with time. In comparison, the African green monkey kidney (Vero) cell line was tested as normal cells to determine the side effects of 5-fluorouracil. The results show that the optimal concentration of 5-fluorouracil is about 500 μM, which presents the best anticancer effect and mild side effects.